Case study: brass band management in secondary school SM Shan Tao, Likas, Kota Kinabalu, Sabah / Janetlyn Solynsem - Solynsem, Janetlyn (2009)
This study is a case study about the brass band management in secondary school. The study was conducted to determine brass band management in secondary schools. The objective are determine the background Shan Tao Secondary School band, to know the brass band management at Shan Tao Secondary School in terms of teachers responsibilities, finance, facilities and equipment, musical instruments, to know the challenges and problems faced in the brass band management, and to find out how the teachers overcome the problems faced in managing the brass band. The researcher was interviewed three from six band teacher in this band. Result shows that the band management in this school is very effective in terms of teacher responsibilities, band members' commitment, financial, facilities and equipment, music instruments and supports.